Deciphering the Molecular Nexus: RNF20 as a Critical Mediator at the Epigenetics-Metabolism Interface in Driving Lung Cancer Progression - Singh, Anshu; Justus Liebig University Giessen (My University, 2024)
Lung cancer is the most common cancer and the leading cause of cancer-related deaths in both men and women around the world. Despite advances in lung cancer treatment options, the mortality rate closely parallels the incidence rate. Lung cancer is clearly a global emergency that requires immediate attention. In mammalian cells, the ring finger protein 20 (RNF20) is the major H2B-specific ubiquitin ligase. Its primary function is to monoubiquitinate histone H2B on lysine 120 (H2Bub). On a cellular level, RNF20 suppresses the expression of several proto-oncogenes, which reside preferentially in closed chromatin and are modestly transcribed. On one hand cell culture based studies have shown that RNF20 reduction enhanced the transcriptional effects of epidermal growth factor (EGF), boosted cell migration, and induced transformation and cancer. On the other hand, RNF20 is found to be required for MLL-rearranged leukemia. Despite several advancements in the study of RNF20 function in cancer development, its role is still debatable. As a result, I sought to shed light on the cancer development and progression. To study the role of RNF20 in cancer development, I used a genetic mouse model of Rnf20 loss of function (LOF). Global ablation of Rnf20 caused pre-implantation embryonic lethality. Interestingly, Rnf20+/- mice were viable and fertile but had a significantly higher incidence of spontaneous tumors in the lungs. Immunohistochemical analysis revealed that these spontaneous lung tumors belonged to the small cell-like lung cancer (SCLC) phenotype and adenocarcinoma. SCLCs were more common. For the mechanistic characterization, I used an in vitro cell culture model. I made Rnf20 loss of function MLE-12 cells by crispr-Cas9 as well as siRNA mediated silencing of Rnf20 in NCL-H82 cells. In cell culture assays, I discovered that RNF20 depletion induced epithelial-mesenchymal transition (EMT) and facilitated cell migration and invasion. I noticed an increase in DNA damage in Rnf20-depleted cell culture models and delayed DNA damage repair, which was also confirmed in the lungs of Rnf20+/- mice. Glucose uptake, lactate secretion, and extracellular acidification rate (ECAR) assays in RNF20 depleted cells revealed that RNF20 depletion increased glycolytic activity in lung cells. Furthermore, metabolomics profiling revealed a significant increase in the level of metabolites following RNF20 depletion. Recent research has shown that HIF1a overexpression plays a significant role in tumor growth and metastasis by initiating angiogenesis and regulating cellular metabolism to overcome hypoxia. In my research, I discovered that RNF20 depletion significantly increased the level of HIF1a in lung cells. Furthermore, when RNF20 is depleted, the HIF1a signaling pathway is activated, and as a result, the metabolic profile of Rnf20 LOF cells is dramatically altered, as is their invasive and migratory ability. After knocking down Hif1a, I was able to partially rescue the glycolytic and invasive phenotype of Rnf20 LOF cells. In conclusion, my study revealed an important role for the RNF20-HIF1a axis for critical metabolic reprogramming in lung carcinoma, pointing to these proteins as potential targets for lung cancer therapeutic intervention.
Keywords: ddc:570